Teachers’ Use and Attitudes towards ICT A case of Teachers at Bejaia Department of English - ALIOUCHOUCHE-KACI, Fadhila (Université de M'sila, 2018)
The purpose of this study is to investigate teachers’ use and attitudes towards Information and Communication Technology that is ICT, at the department of English, Bejaia University. The researcher relied on the descriptive research method. The necessary data was collected by a questionnaire designed and distributed to the teachers of the aforementioned department. The main findings of the research revealed that a majority of the respondents acknowledged the importance of ICT in language teaching. However, it is worth mentioning that for some participants, the use of ICT at the department of English is still at its embryonic state because of different obstacles teachers face in implementing these modern tools in their classes.
Keywords: teachers-ICT-language teaching- learning process-teachers’ attitudes- ICT use